2005
DOI: 10.2174/138955705774329528
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Prodrug Design

Abstract: The background of prodrug design is presented herein as the basis for introducing new and advanced latent systems, taking into account mainly the versatility of polymers and other macromolecules as carriers. PDEPT (Polymer-Directed Enzyme Prodrug Therapy); PELT (Polymer-Enzyme Liposome Therapy); CDS (Chemical Delivery System); ADEPT(Antibody-Directed Enzyme Prodrug Therapy); GDEPT/VDEPT (Gene-Directed Enzyme Prodrug Therapy/Virus-Directed Enzyme Prodrug Therapy); ODDS (Osteotropic Drug Delivery System) and LEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 42 publications
0
14
0
3
Order By: Relevance
“…However, the acidic property of Nova2 (513246-99-6) should be taken into account for its oral delivery measure, as it could inflict certain hazard for heartburn patient. In this end, prodrug construction should be considered in its synthesis strategy [63]. …”
Section: Resultsmentioning
confidence: 99%
“…However, the acidic property of Nova2 (513246-99-6) should be taken into account for its oral delivery measure, as it could inflict certain hazard for heartburn patient. In this end, prodrug construction should be considered in its synthesis strategy [63]. …”
Section: Resultsmentioning
confidence: 99%
“…Relating (6) to (9) and bearing in mind that variance is proportional to diffusion coefficient, it can be shown that…”
Section: Diffusion-only Molecular Propagation Modelmentioning
confidence: 99%
“…Molecular communication (MC) is realized through the transmission and reception of biochemical information encoded in the concentration and type of molecules. The emergence of MC has found potential applications in fields that include bioengineering [2,3], nanomedicine [4][5][6][7][8][9][10], and environmental safety [11]. Readers shall refer to [1,[12][13][14][15][16] and the references therein for reviews of recent work in MC as well as some potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…These will include advances in pharmacology directed towards TDD, transport mechanisms for conveying the drugs to the targeted site, and the functional mechanism for administering the drug to the specific site. Pharmacological substances like prodrug [7,8] and nanomachines such as nanobots [9][10][11][12], provide functionalities that can be used in TDD. The application of MC to TDD using biological nanomachines has been introduced by Nakano et al [13].…”
Section: Introduction Molecular Communication (Mc) Is a New Researmentioning
confidence: 99%